Pituitary Gland Functional Connectivity and BMI - Rucker, Paige; Ikuta, Toshikazu (Frontiers in Neuroscience, 2019)
The pituitary gland (PG) influences body weight through hormonal releases; however, the relation between body weight and PG’s co-activities with other brain regions remains unclear. Here, we aimed to identify (1) the functional connectivity of the PG and (2) PG functional connectivity associated with body mass index by examining resting state functional magnetic imaging (rsfMRI) data. Using enhanced Nathan Kline Institute-Rockland Sample, PG functional connectivity of 494 individuals was analyzed to assess in voxel-wise fashion. A negative association was found between BMI and PG functional connectivity with the orbitofrontal cortex, hippocampus, putamen and temporal lobe. Our results show PG dysconnectivity to these regions is associated with higher BMI and implicate that the connectivity between these dopaminergic regions and PG is associated with body weight maintenance through feeding behavior and growth.